Understanding International Similarities and Differences in Corporate Community Involvement: The Case of Capital One - Amerman, Taylor (2012)
Corporate Social Responsibility (CSR) is a highly dynamic and contestable concept in today’s global marketplace (Matten & Moon, 2004). One area of CSR is Corporate Community Involvement (CCI) or a “corporation’s engagement with local communities, special interest groups and issues of concern, above and beyond the day-to-day operations, often working in partnership with not-for-profit organizations” (Tuffrey, 1998). CCI drives business decision-making to make a significant and sustainable impact in communities around the world. At the same time, CCI practices vary from firm to firm and country to country. To gain a better understanding of CCI internationally, this dissertation asks what explains the similarities and differences in CCI between different countries? This research is located within existing research on CSR and CCI. It then uses institutional theory to evaluate the cultural contexts of CCI in the United States of America (USA) and the United Kingdom (UK).